Pembuatan Media Herbarium Kering Dalam Pembelajaran Dikotil dan Monokotil di Madrasah Ibtidaiyah - Muhammad Suwignyo Prayogo; Umi Salamatus Sakdiyah; Ning Fafa Fashokha (Jurnal IAI Bunga Bangsa Cirebon, 2023)
This study aims to determine the effect of dry herbarium learning media on students' enthusiasm in the learning process. This type of research is qualitative with data collection methods in the form of observation, interviews, documentation, and practice. Before starting to make learning media, students get an explanation of the material presented by researchers regarding dicot and monocot plants. After that, the students did a simple practice of making herbarium learning media with plants such as rice, chili, and papaya. In practice, students are divided into four groups according to their seats. The object of the research were 22 students of class IV MIMA Salafiyah, Kedunglangkap, Kencong, Jember. From the implementation of the research that has been done, the results of the research show the enthusiasm of the students which is very clear, especially when doing the practice of making herbarium learning media and answering questions asked before ending the lesson. Like the classification of rice, laurels, and papaya plants, they are classified as dicots or monocots. In addition, through practice it can also train students to work together in completing the making of herbarium learning media. Keywords: herbarium; practice; MI/SD